Piotra Chmielowskiego argumenty przeciw poetom i poezji (w Zarysie literatury z ostatnich lat szesnastu) - Ratajczak, Wiesław (Poznańskie Studia Polonistyczne. Seria Literacka, 2012)
The article discusses the arguments against poetry that were used in Piotr Chmielowski’s Zarys literatury polskiej z ostatnich lat szesnastu [An outline of the literature of the last sixteen years] by its author. The critic’s intention was to diminish the significance of poetry and, in effect, to push poetry to the margin of literary life. To achieve that, Chmielowski presented a number of examples where modern poetry was not capable of grappling with the problems and challenges of the modern world. Chmielowski also instilled a vision in which writing poems itself appeared to be atavistic and as a relic of an earlier stage of evolution. Since lyric poetry made a particular core of literature, to challenge its position in literature in the name of progress made it possible to question all traditional “authorities”. The author of Zarys indicated examples testifying to the vitality of the novel and future possibilities in the development of this particular genre, whereas his formulated accusations against poetry and poets included their general bad condition (physical, mental and psychical). In addition, Chmielowski accused poetry of insincerity and untruthfulness. With regard to the poetics of the discussed poems, Chmielowski just limited himself to briefly formulated allegations and objections of their rhetoricality and epigonic character.